2021
DOI: 10.1093/mnras/stab1953
|View full text |Cite
|
Sign up to set email alerts
|

The influence of streaming velocities and Lyman–Werner radiation on the formation of the first stars

Abstract: The first stars in the Universe, the so-called Population III stars, form in small dark matter minihaloes with virial temperatures Tvir < 104 K. Cooling in these minihaloes is dominated by molecular hydrogen (H2), and so Population III star formation is only possible in those minihaloes that form enough H2 to cool on a short timescale. As H2 cooling is more effective in more massive minihaloes, there is therefore a critical halo mass scale Mmin above which Population III star formation first becomes pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 78 publications
1
53
1
Order By: Relevance
“…Thus, more prevalent Pop III star formation results in stronger constraints on the WDM mass. Recent simulations of feedback effects on the first halos (Kulkarni et al 2021;Schauer et al 2021) suggest a shallower relationship between the LW background intensity and minimum mass than was found in early work (e.g., Machacek et al 2001). This implies that for a given LW background intensity, the overall impact of feedback will be weaker (see also Skinner & Wise 2020), giving rise to the possibility of more Pop III star formation (as M min,iii rises more slowly).…”
Section: Likelihood Input Covariancesmentioning
confidence: 86%
“…Thus, more prevalent Pop III star formation results in stronger constraints on the WDM mass. Recent simulations of feedback effects on the first halos (Kulkarni et al 2021;Schauer et al 2021) suggest a shallower relationship between the LW background intensity and minimum mass than was found in early work (e.g., Machacek et al 2001). This implies that for a given LW background intensity, the overall impact of feedback will be weaker (see also Skinner & Wise 2020), giving rise to the possibility of more Pop III star formation (as M min,iii rises more slowly).…”
Section: Likelihood Input Covariancesmentioning
confidence: 86%
“…In a-sloth, Pop III stars form instantly in a single star burst in a mini-halo (haloes below the atomic cooling threshold (Tvir = 10000 K) as soon as its virial mass exceeds Mcrit. By default, we follow the prescriptions given in Schauer et al (2021, their Eqs. 9 and 10) and Hummel et al (2012, their Eq.…”
Section: Population III (Pop Iii) Starsmentioning
confidence: 99%
“…1) to determine Mcrit. Schauer et al (2021) showed that the critical mass is dependent on the LW background and the large-scale streaming velocity of the baryons relative to the dark matter: log10Mcrit,S21 = 6.0174 (1.0 + 0.166…”
Section: Population III (Pop Iii) Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous models, when using a-sloth we do not explicitly account for the effect of Lyman-Werner (LW) radiation (Machacek et al 2001;Schauer et al 2021) or supersonic baryon streaming (a residual velocity difference between dark matter and baryonic matter resulting from recombination, Tseliakhovich & Hirata 2010) which are expected to affect Tcrit in a nonuniform manner (e.g. Fialkov et al 2012;Schauer et al 2019a).…”
Section: Basic Semi-analytical Modelmentioning
confidence: 99%